2008
DOI: 10.1038/modpathol.3800978
|View full text |Cite
|
Sign up to set email alerts
|

Malignant germ cell tumours in the elderly: a histopathological review of 50 cases in men aged 60 years or over

Abstract: Malignant testicular germ cell tumours in the elderly are extremely rare with anecdotal accounts of their aggressive behaviour. Fifty cases of germ cell tumour, diagnosed at the age of 60 years or above, were pathologically reviewed. The oldest patient was 86 years of age, with 78% of cases presenting in men in their 60s. Forty-one (82%) of the tumours were seminomas with only nine cases (18%) of mixed or nonseminomatous germ cell tumour. However, all non-seminomatous types of tumour were represented in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…9 Similarly, a histopathologic study of 50 men with GCT diagnosed at age 60 years found larger primary tumor size and more frequent lymphovascular invasion and rete testis involvement compared with historical controls of all ages. 15 In contrast, a recent retrospective series found 77% of 60 patients diagnosed at 60 years presented with stage I disease, 16 comparable with rates in younger patients. 17,18 Although our study does not allow direct comparison of stage distribution for older versus younger men, stage and initial treatment are provided for 166 GCT patients who presented to MSKCC at 50 years.…”
Section: Discussionmentioning
confidence: 93%
“…9 Similarly, a histopathologic study of 50 men with GCT diagnosed at age 60 years found larger primary tumor size and more frequent lymphovascular invasion and rete testis involvement compared with historical controls of all ages. 15 In contrast, a recent retrospective series found 77% of 60 patients diagnosed at 60 years presented with stage I disease, 16 comparable with rates in younger patients. 17,18 Although our study does not allow direct comparison of stage distribution for older versus younger men, stage and initial treatment are provided for 166 GCT patients who presented to MSKCC at 50 years.…”
Section: Discussionmentioning
confidence: 93%
“…Information is scarce in the available literature regarding the clinical outcome of older patients with malignant germ cell tumours in the era of platinum‐based chemotherapy, with just a few case reports of successful treatment [9–11]. A recent pathological review [2] of 50 germ cell tumours in the elderly (median age 67 years) found that most were seminomas (82% compared to the 73% reported in the series of the present study); however, complete information about staging or outcome was not given. This report[2] suggested that older patients presented with more locally advanced disease than younger patients; however, this has not been the experience in our series, where 77% of patients presented with stage I disease, which is similar to other contemporary series in a non‐age selected population [12].…”
Section: Discussionmentioning
confidence: 99%
“…Non‐seminoma occurs at a median age of 27 years, and seminoma at a median age of 37 years. Patients also present into older age, typically with comorbidity, and with presentation at a later stage [2]. The incidence of testicular cancer is increasing, with a doubling of new cases diagnosed in Great Britain between 1975 and 2007, to an age standardized rate of 6.6 per 100 000 population.…”
Section: Introductionmentioning
confidence: 99%
“…Methodologically data from all federal states in Germany showed a high percentage of data completeness which is important for reliability of our findings. Our demographic analysis confirmed older age for seminoma patients compared to non‐seminoma patients which is consistent with other recent and earlier reports from the 1990s (Stone et al ., ; Agnarsson et al ., ; Berney et al ., ; Ruf et al ., ). The age difference between both entities in our study was 9 years and is reported to range between 6 and 9 years between seminoma and non‐seminoma patients (Agnarsson et al ., ; Ruf et al ., ).…”
Section: Discussionmentioning
confidence: 99%